2022
DOI: 10.1177/17470218221145314
|View full text |Cite
|
Sign up to set email alerts
|

Humans can monitor trial-based but not global timing errors: Evidence for relative judgements in temporal error monitoring

Abstract: Humans can monitor the magnitude and direction of their temporal errors on individual trials. Based on the predictions of our model of temporal error monitoring that rely on a relative comparison of internal clock readings, we predict that participants would monitor their timing errors in individual trials, but not the direction of their global timing errors without external feedback. One study has indeed found that accurate self-monitoring of average timing biases required external feedback with directional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
2
7
1
Order By: Relevance
“…By revealing the modulatory effects of temporal unpredictability on performance monitoring, our study complements the recent literature demonstrating that humans possess an ability to monitor their timing errors better than chance (Kononowicz et al, 2018;Öztel & Balcı, 2022;Riemer et al, 2019). This metacognitive capability has been even found in rodents, suggesting the evolutionary significance of temporal error judgments (Balci, 2022;Kononowicz et al, 2022).…”
Section: Discussionsupporting
confidence: 77%
“…By revealing the modulatory effects of temporal unpredictability on performance monitoring, our study complements the recent literature demonstrating that humans possess an ability to monitor their timing errors better than chance (Kononowicz et al, 2018;Öztel & Balcı, 2022;Riemer et al, 2019). This metacognitive capability has been even found in rodents, suggesting the evolutionary significance of temporal error judgments (Balci, 2022;Kononowicz et al, 2022).…”
Section: Discussionsupporting
confidence: 77%
“…These findings support the idea that human participants' metacognitive abilities previously observed in 2AFC paradigms generalize to temporal error monitoring. These findings were replicated by , where participants were tested in a temporal production task and rated their error magnitude (and direction) on a slider scale (see also Öztel et al, 2021;Öztel & Balcı, 2023a).…”
Section: Metric Error Monitoring: a New Approach To Conscious Monitoringmentioning
confidence: 83%
“…Riemer et al (2019) showed that correct monitoring of overall temporal biases occurred only when trial‐based feedback included error direction information. However, Öztel and Balcı (2023a) did not find the same effect of trial‐based feedback on the global monitoring of temporal biases. These findings collectively suggest that monitoring overall temporal biases on a global scale might not be feasible without trial‐by‐trial feedback that includes directional and magnitude information, as indicated by Riemer et al (2019).…”
Section: Metric Error Monitoring: Different Operationalizationsmentioning
confidence: 94%
See 2 more Smart Citations